Analisis Faktor Pengembangan Organisasi Melalui Penguatan Kompetensi SDM di SDN 52 Parupuk Tabing - Sabrina Oktavia (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the factors influencing organizational development through strengthening human resource competence at SDN 52 Parupuk Tabing, focusing on the roles of external factors such as education and economics. Organizational development is a planned process to enhance organizational effectiveness by changing the behavior of its members, making it crucial in educational institutions. SDN 52 Parupuk Tabing has implemented development programs like in-depth learning training and coding training for teachers and administrative staff. This research employed a descriptive qualitative approach to deeply understand the phenomena through direct interaction with research subjects and describing data in words. The research subjects were the school principal, teachers, and administrative staff. Data collection techniques included observation, interviews, and documentation. The findings indicate that the school successfully implemented organizational development principles through a synergy of internal factors (participative leadership, clear structure, and intrinsic motivation) and external factors (adaptation to technology, support from educational policies, and economic resource management). The success highlights that an education organization oriented toward innovation and technology, supported by participative leadership and a collaborative culture, can enhance effectiveness, professionalism, and competitiveness in the digital era.